Implementasi civic disposition peserta didik di Kurikulum Merdeka - Triaswari, Finanda Dwi; sutrisno, Sutrisno; Asmaroini, Ambiro Puji (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research is a mixed method with an analytical study approach at SMK PGRI 2 Ponorogo, especially in class X. As for this research, in collecting data using interviews, questionnaires, and documentation procedures. Data analysis techniques by classifying, reducing and eliminating unnecessary data, are then presented descriptively. in order; 2) learning in Pancasila education subjects through monitoring and Projects to Strengthen Pancasila Student Profiles (P5); 3) commitment between teachers as an effort to help implement and develop students' civic character; 5) evaluation through supervision to find out how the character progresses in students for future improvements and maximizes the strengthening of civic disposition at school.